Digital Currencies in Light of Artificial Intelligence, Effects and Negatives: Iraq is An Example (International Journal of Financial, Administrative and Economic Sciences, 2024)
The digital monetary system in the modern era is based on money. It occupies a leading position in economic studies and in all current economic transactions. It is a digital cash system, an advanced system for electronic money that was invented by unknown parties in 2008. The main goal behind its invention was to get rid of the capitalist system and the official authorities’ control over the issuance of digital currencies and to come up with a new technology that, with its technological confidence, replaces the role of control and supervision in central banks, that is, in light of artificial intelligence. Dealing with it has been banned in Iraq because it leaves effects and problems on the economic level that cannot be easily overcome. This topic was addressed through two sections. The first dealt with research into encrypted digital currencies in terms of their economic nature, while we devoted the second section to researching and clarifying how to invest in them and their negative and positive economic effects digital currencies electronic money, artificial intelligence.
Keywords: Cryptocurrencies; Virtual Currencies